An Analysis of The Strengths of Arguments of the 2012 United States’ Presidential Debate: The Case of Barrack Obama Vs Mitt Romney - Herlin Octaviani (Passage, 2014)
The study aims to measure arguments’ strength of the 2012 the United States’ presidential candidates, Barack Obama and Mitt Romney, in their latest presidential debate. The researcher selected 41 arguments from the debate transcription, based on the completeness requirement of the primary elements of Toulmin’s Argumentation Model (1958), such as claim, ground and warrants. The data are analyzed through the three stages of analysis, namely cogency analysis, soundness analysis, and strength level analysis. Based on the data analysis, three qualifications are found: strong argument, weak argument and very weak argument. The analysis shows that Barrack Obama is the winner of the latest U.S presidential debate. Obama won the debate because his strong arguments’ frequency is higher than Romney’s strong argument in the debate. Furthermore, most of Obama’s arguments, either strong or weak, are constructed in the form of deductive arguments. As the nature of deductive argument, which guarantees the cogency and the validity of its conclusion, Obama’s arguments in the latest presidential debate 2012 are mostly cogent and valid.Keywords: Argument Strength, Cogency Analysis, Soundness Analysis, Strength Level Analysis